Issues and opinions in the understanding of the theoretical basis of peace education (2002)
This paper discusses the understanding of issues and opinions relating to peace education in fostering the development of culture of peace wherein an individual, community will strive to maintain peace and resolve conflict in a non-violent way. The paper looks at guiding principles of educational policy on education for peace, five approaches to peace education, scope of peace education and objectives of peace education. The paper conclude by looking at gains that communities, work environments will gain in form of harmonious living and violence free conflict resolution strategies if peace education is fully implemented.